To Apply, to Debunk, to Perform. - Piotr Zamojski (Wydawnictwo Uniwersytetu Gdańskiego, 2023)
In this article I propose and examine a distinction between three types of educational theory: technical, critical and affirmative (or post-critical). These three different types of theoretical engagement in education are conceived of in terms of ideal types (following Weber 1958). Naturally, this categorisation is not exhaustive for the field of educational theory, however, it is important to note that the emergence of each type is related to a particular momentum in the historical development of the West. The technical type genealogically comes from the idea of modern science and its attempt to produce knowledge that would give to humans the means to gain power over nature (cf. Bacon 2003). This means that within this type one aims to describe the causal relations, i.e. the laws governing a particular domain of the world. This way of reasoning is well adopted in educational sciences, and it is important to understand its consequences for education itself. The critical type can be derived from the project of critical theory (e.g. Horkheimer and Adorno 2002), which after the Shoah made clear that the widespread domination of instrumental reason is dangerous, and can make ordinary people take part in radical evil. Hence, the task of critique, of reviving and sustaining critical reason (Adorno 2004). The most well known educational rendering of this paradigm is the project of critical pedagogy. By following the insights of Elisabeth Ellsworth (1989), Ilan Gur-Ze'ev (1998), Jacques Rancière (1991, 2003), Peter Sloterdijk (1987), and Bruno Latour (2004) it is possible to investigate the limitations and potential dangers of both: critical theory and critical pedagogy. Such a critical analysis of the critical position will take us to a new type of educational theories that is currently emerging in the field. Together with Naomi Hodgson and Joris Vlieghe (2017) we have named these as post-critical (which from the very beginning was a tentative name). These theories are indeed post-critical in the sense that they come after the critique, that they presuppose a critical inquiry, and critical knowledge - but they seek to make a further move, a step beyond (or simply after) critique. They are affirmative, in the sense that they point to a particular educational practice or arrangement (e.g. school, lecture, studying, teaching, seminar, etc.) that is either dwarfed, forgotten, or supressed (also by radical critique itself) in order to affirm it, to speak out its inherent value, to remind pedagogues / educationalists / practitioners what we are engaged in, what is that we practice, and what is the inherent worth of it. Hence, these theories are also immanent, as they make the effort to speak out education on, and with its own terms, and also, these theories are performative, as they form a range of thought (a conceptual horizon) within which we can act educationally. In the conclusion few examples of such a theories will be briefly put at display.